Thermo-phototronic effect in p-type Na-doped SnS single crystals for enhanced self-powered photodetectors. (October 2021) - Ouyang, Bangsen; He, Wenke; Wu, Liyun; Zhao, Li-Dong; Yang, Ya
Abstract: Thermoelectric and photoelectric effects are two dominant mechanisms to realize heat- and light-to-electricity conversation and are widely applied to design generators and sensors. To better boost the efficiency or enrich the function of these devices, thermoelectric and photoelectric effects are simultaneously introduced into a single device recently. Most notably, both n- and p-type semiconductors serve as the basic building blocks of these devices. However, there is no research work that investigates the effect when both thermoelectric and photoelectric effects are integrated into a p-type semiconductor. Here, a Na-doped SnS single crystals—a p-type multi-functional material with exceptional thermoelectric and photoelectric performances—was leveraged to fabricate the enhanced self-powered photodetector, in which the thermo-phototronic effect can significantly boost the output performance of the device. At a temperature difference of 3.9 K, the coupling enhancement ratio of photocurrent and photovoltage under a light intensity of 20 mW/cm 2 are 26.7% and 31.8%, respectively. The coupling enhancement of the output signals may be associated with the acceleration of the photogenerated holes induced by the driving force of the thermoelectric effect. This work laid the foundation for developing higher-performance photodetectors, generators, and multi-functional sensors. Graphical Abstract: ga1 Highlights: We have presented the thermo-phototronic effect in a p-type sodium doped tin sulfate (SnS) single crystals. At a temperature difference of 3.9 K, the coupling enhancement ratio of photocurrent and photovoltage under a light intensity of 20 mW/cm 2 are as high as 26.7% and 31.8%, respectively. The fabricated device shows great potential in higher-performance photodetectors.